La prima cooperazione euromediterranea: il caso tunisino (1976-1987) - De Leo, Nancy (Studi Politici, 2025)
In the early 1970s, the EEC launched the comprehensive Mediterranean policy with the aim of strengthening its political and economic role in the area. The emergence of the countries of the Global South, the Middle East question and competition between the superpowers made the Mediterranean a strategic area for European interests. The agreement between the EEC and Tunisia signed in 1976, fell within this framework, which provided for the strengthening of economic, financial and social relations between the two shores of the Mediterranean. The outcome of the cooperation agreement fell short of expectations: the Tunisian and EEC markets competed with each other, spurred by the economic crisis and the further EEC enlargement to other European Mediterranean countries. Changes in the Mediterranean non-member countries in the 1980s, as well as international political and economic transformations, reoriented the objectives of the EC cooperation policy toward the area and, more broadly, toward developing countries.